2015
DOI: 10.1364/oe.23.012328
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a versatile pulsed laser source based on a diode seed and ultra-high gain bounce geometry amplifiers

Abstract: We present an investigation of a versatile pulsed laser source using a low power, gain-switched diode laser with independently variable repetition rate and pulse duration to seed an ultra-high gain Nd:YVO4 bounce geometry amplifier system at 1064nm. Small-signal gain as high as 50dB was demonstrated in a bounce geometry pre-amplifier from just 24W pumping, with good preservation of TEM00 beam quality. The single amplifier is shown to be limited by amplified spontaneous emission. Study is made of further scalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although the shortest pulses have been longer than that of the ML semiconductor lasers, the flexibility of the pulse shaping and also repetition rate and their high robustness are their unique strength [13][14][15] . In particular, gainswitched semiconductor lasers combined with rare-earth-doped fibre linear amplifiers in a master-oscillator-power-amplifier configuration have significant advantages because of the highly controllable optical pulses, such as variable repetition rate, arbitrary timing operation, flexible pulse duration, waveform spectral control and synchronization to electrical triggers, in addition to the robustness and stability [16][17][18][19][20] . It was recently reported that additional non-linear pulse shaping in optical fibres can generate femtosecond pulses 21,22 .…”
mentioning
confidence: 99%
“…Although the shortest pulses have been longer than that of the ML semiconductor lasers, the flexibility of the pulse shaping and also repetition rate and their high robustness are their unique strength [13][14][15] . In particular, gainswitched semiconductor lasers combined with rare-earth-doped fibre linear amplifiers in a master-oscillator-power-amplifier configuration have significant advantages because of the highly controllable optical pulses, such as variable repetition rate, arbitrary timing operation, flexible pulse duration, waveform spectral control and synchronization to electrical triggers, in addition to the robustness and stability [16][17][18][19][20] . It was recently reported that additional non-linear pulse shaping in optical fibres can generate femtosecond pulses 21,22 .…”
mentioning
confidence: 99%
“…There are two general methods for making picosecond seed lasers. One was the Stimulated Brillouin Scattering (SBS) pulse compression technology [7][8][9][10][11][12] and the other one was the microchip laser technology [10,[13][14][15][16][17][18]. Microchip laser by the Diode Pumped Solid State (DPSS) laser was a relatively small resonator, which could be producing picosecond seed laser.…”
Section: Introductionmentioning
confidence: 99%
“…Providing its higher harmonics at 532 nm and 355 nm, diode-pumped Nd:YAG laser system has only a discrete single frequency as its primary fundamental laser line at 1064 nm. This dictates the utilization of optical parametric conversion methods in these systems for wavelength tunability, causing not only higher complexity and cost but also lower system reliability and efficiency [2][3][4]9]. Thus, today, the most common alternative approach is the vibronic solid-state laser materials with pulse generation and wavelength tunability capabilities by directly diode laser pumping.…”
Section: Introductionmentioning
confidence: 99%